All are not created equal: Assessing initial driving self-regulation behaviors among older adults. (March 2022) - Vivoda, Jonathon M.; Molnar, Lisa J.; Eby, David W.; DiGuiseppi, Carolyn; Jones, Vanya; Li, Guohua; Strogatz, David; Yung, Raymond; Nyquist, Linda; Smith, Jacqui; Zakrajsek, Jennifer S.; St Louis, Renée M.; et al.
Abstract: Introduction: Mobility is closely tied to the ability to safely drive. In older adulthood, many people begin to avoid difficult driving situations, such as driving at night, during rush hour, on freeways, or in unfamiliar areas. Reasons for such avoidance include driving self-regulation (SR; an intentional response to perceived difficulty), lifestyle changes, or preference. Most previous research has not made distinctions between these reasons, has not compared driving avoidance situations, and has not differentiated between those early in the SR process from those farther along. This study addressed those issues by comparing each of the aforementioned driving avoidance behaviors as one's initial SR behavior. Methods: A total of 1554 older drivers from the AAA Longitudinal Research on Aging Drivers study were analyzed. Multinomial regression was used to determine how demographics, function, and driving-related factors were related to a difference in the odds of reporting one initial SR behavior compared to each of the others. Results: The most common initial SR behavior was avoidance of nighttime driving (57.59%), followed by avoidance of rush hour driving (26.96%), driving in unfamiliar areas (10.81%), and driving on freeways (4.63%). A variety of demographic and function variables were associated with a difference in the odds of the initial SR behaviors, including gender, race, income, anxiety, driving responsibility, having rides available, driving abilities, and driving comfort. Conclusions: Nighttime avoidance is the most common initial SR behavior. Variables specifically related to situational driving comfort and driving ability were the best predictors of differences in driving SR. Highlights: Avoidance of driving at night was the most common initial self-regulation behavior. Situational driving comfort was the best predictor of self-regulation differences. Differences in self-regulation were also related to driving ability and vision. Gender, income, work status, and providing rides also predicted a difference. Understanding these differences provides a clearer appraisal of risk and well-being.